DESCRIPTION OF RESILIENCE IN CHILDREN WITH SUFFERING LEUKEMIA CANCER - Miftah Nurkhaerati; M. Ahkam A (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Children suffering from leukemia often have to face quite difficult developmental tasks, as well as having to overcome the impact of the disease they suffer from, therefore it is important to look at the child's resilience during the treatment period. This research aims toto find out how the process of building resilience in children suffering from leukemia cancer, as well as the strengthening and encouragement that the subject receives during the treatment period, thus forming a resilient individual. The method used in this research is a qualitative research method with an intrinsic case study approach. Data was collected through interviews with three respondents who were children suffering from leukemia and four other significant others.The results of the research show that children who experience leukemia must have three components of resilience to achieve resilience. The first component is I have, where the respondent realizes that he or she has received support from other individuals around him, after that, I am, which is the belief and strength within the individual, and I can, which is the effort made by the individual in the process of solving the problems faced.